Empowerment of Farming Communities to Increase Production Through the Use of Agricultural Machinery in Corn Cultivation Activities in Sitiung Village Dharmasraya Regency - Mislaini Rahman; Tuty Anggraini; Nurwanita Ekasari Putri; Aries Kusumawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
This community service activity aligns with the Student KKN activities in Nagari Sitiung, Sitiung District, Dharmasraya Regency. The integrated community partnership program with student activities is carried out to increase corn production through technology transfer using wooden or bamboo hoes with semi-mechanical corn planting tools. The activity methodology is carried out by approaching corn farmers at the Nagari Sitiung partner location, Sitiung District, Dharmasraya Regency, through data collection and counseling activities with a participatory approach. Furthermore, corn planting tools were introduced through training and demonstrations on the corn farmer's land in Nagari Sitiung. So far, many farmers have planted corn manually. This causes a relatively long planting process because the land is very large. The rolling planter corn planting tool provides various significant benefits for corn farmers because it can help increase the efficiency of time and energy in the planting process, thereby accelerating the production stage. This tool also reduces dependence on human labor, directly reducing operational costs. In addition, this corn planting tool can improve the accuracy of planting distances, which helps optimize land production and produces more uniform plants, and it has the potential to increase yields.